MERAJUT NALAR FIQH KONTEKSTUAL - Sanusi Sanusi (Program Studi Hukum Keluarga Islam, 2015)
The notion of contextualization of Islamic law is a form of initiative actualization of the value substance of Shari’ah ideals that in the elucidation and formulation of law put forward in the consideration of social reality. In reality, the change is a necessity; everything flows with the current developments and the changing times. Included in it, that social problems continue to grow and need to find the solution that is able to accommodate it answers. The starting point of this idea is oriented to the concept of Islamic law dimension to the social reality as a framework to formulate a foothold in the building of Islamic law. Benefit in this context being the point of important points that are the foundation of contextual understanding. The consequence of the contextualization of the idea of Islamic law (fiqh) is a framework methodology of ijtihad trying to connect with a variety of approaches, both historical approach, social, cultural, legal and others. Purity is important view of Islamic law (fiqh) for most groups of Muslims as a legacy of its history and the results of intellectual work that is constructed over a century ago should be viewed proportionally, so it will be protected from static understanding of patterns, exclusive, frozen and stiff.